Relationship between different methods of visualization of hip joint lesions in patients with axial spondyloarthritis during a two-year observational study - E. M. Agafonova; Sh. Erdes (Научно-практическая ревматология, 2022)
Almost half of the patients with axial spondyloarthritis (axSpA) in Russia have hip joint lesions (HJD), but the causes and rates of its progression have not been studied.Aim. To assess the relationship of X-ray progression with MRI data of hip joint examination in patients with axial spondyloarthritis during a two-year follow-up.Material and methods. We analyzed 77 patients (23 women and 54 men) with axSpA (ASAS criteria, 2009), followed for at least 2 years with clinical and/or instrumental signs of coxitis. After 2 years, the patients underwent a complete clinical, laboratory and instrumental examination (MRI and radiography of the hip joint) again. Their average age was 30.8±7.7 years, with an average disease duration of 74.0±90.3 months. 72 (94%) patients were HLA-B27 positive. In all patients, the BASRI-Hip index was assessed for each hip joint. The median values of laboratory parameters of inflammation – erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) level – were initially high (20.0 mm/h and 14.5 mg/l respectively), but after 2 years the indicators decreased: ESR – down to 8.0 mm/h, and CRP – down to 5.0 mg/L (p<0.05). The median values of the BASDAI also decreased over 2 years of active observation from 4.5 to 2.2 (p<0.05). The value of the ASDAS-CRP index was high and corresponded to 3.1±1.1 and after 2 years also decreased down to 1.94±1.0 (p<0.05). Pain in the hip joint was detected in 66 out of 77 patients (86%) at the time of inclusion, and 2 years later – in 48 (62%) (p<0.05). As for other clinical manifestations of the disease at the time of inclusion in the study, among 77 patients, 75% had peripheral arthritis, and after 2 years – only about 39% (p<0.05). The patient’s functional index (BASFI) was initially 3.3, and after 2 years it decreased down to 1.3 (p<0.05).Results. At inclusion in the study, 59 patients had no radiological changes in the hip joint (BASRI-hip<2). 2 years after the start of follow-up, the number of patients with radiological changes in the hip joint was 48 (62%). Initially, according to MRI, synovitis was detected in 75 (97%), and osteitis – in 23 (30%), chronic changes were present in 2 (3%) patients. After 2 years, synovitis persisted in 46 (60%) (p<0.05), bone marrow edema – in 17 (22%) (p>0.005), and the number of chronic changes increased up to 29 (38%). In 25 (32%) MRI patients, signs of active inflammation were arrested, while only two (13.3%) of them showed the development of chronic changes. To assess the relationship between X-ray progression and MRI signs of inflammation of the disease, patients were divided into two groups according to the total stage of radiographic coxitis (ΔtsrC=0 and ΔtsrC>0). The group with ΔtsrC=0 included 33 patients (22 men and 11 women), and the group with ΔtsrC>0 included 44 patients (32 men and 12 women) (p>0.05). The groups did not differ in clinical parameters such as disease duration, patient age, BASDAI, ASDAS-CRP, BASFI, ESR and CRP (p>0.05). According to MRI, the signs of inflammation (osteitis, synovitis) of the groups also did not differ.Conclusion. The progression of coxitis did not depend on the activity of the disease, on the gender of the patients, and on MRI signs of inflammation in the hip joint.